Faint chemical traces of conspecifics delay settlement of barnacle larvae - Kitade, Shiori; Endo, Noriyuki; Nogata, Yasuyuki; Matsumura, Kiyotaka; Yasumoto, Ko; Iguchi, Akira; Yorisue, Takefumi (Frontiers in Marine Science, 2022)
Larval settlement drives population and community dynamics and evolution of marine invertebrates. While it is well known that larvae sense a variety of biological and environmental factors, there is limited information on how they react to specific factors so as to locate settlement sites. Proteinaceous Waterborne Settlement Pheromone (WSP) was purified from adult barnacles, Amphibalanus amphitrite, in a previous study, but it is unclear how WSP guides barnacle cyprids to the source. Here, a series of settlement assays were conducted to investigate the concentration dependence of recombinant WSP. We report that low concentrations of barnacle WSP decrease the probability of settlement of conspecific cyprids, whereas high concentrations have the opposite effect. We suggest that this is because weak WSP informs cyprids that suitable settlement sites with adult barnacles are distant, inducing them to extend the larval phase. The present study clearly shows that larvae use WSP concentration, rather than presence/absence information. In barnacles, several other conspecific chemical/visual cues also attract larvae. This study opens the door to future research to determine how these cues influence larval behavior in nature.